Um estudo das representações para diferentes GUPS - Moreira, Sthefanny Rupf (2023)
The different proposals for quantum gravity, almost in their entirety, lead to the existence of a minimum length. The introduction of a minimum length causes radical changes in the mathematical description, as well as the physical concepts involved in a theory. In a quantum theory the implementation of a minimum length scenario can be achieved by imposing a minimum uncertainty on the position, obtained through a generalization of the Heisenberg uncertainty principle (GUP). There are different proposals for GUPs. As a result of the minimal uncertainty in position, the operator’s eigenstates are not physical states, which makes the use of position space representation inappropriate. The most natural alternative is to use the moment-space representation. However, to retrieve the information about the position, the quasi-position representation obtained by projecting the state vector onto the states of maximum location is used. The objective of this work is, then, to make a functional analysis of these representation spaces for the main proposals of GUPs, in particular to determine the representations of the position and moment operators in the quasi-position space.